University teaching staff's English language proficiency / Megawati Omar - Omar, Megawati (Academy of Language Studies, 2013)
The public's expectation of a university's teaching staff is the highest possible standards of proficiency of the language used by the community of knowledge and science, of which 'in most parts of the world is English' (Coughlan, 2012). Universities in Asia, Holland, and South Africa state clearly that one of the requirements for their teaching or academic staff is to have good written and spoken English skills. So do universities in Malaysia.